2004
DOI: 10.1002/adma.200400629
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Field Emission of ZnO Nanowires

Abstract: sorbed Pd II . All potentials are reported versus SCE (saturated calomel electrode), although for the scanning tunneling microscopy (STM) experiments a platinum wire was used as a pseudo-reference electrode (E Pt = +0.55 ± 0.05 V vs. SCE). Details about the experimental setup for cyclic voltammetry and STM are described elsewhere [26]. After their preparation, the samples for the photoemission experiments were immediately stored under an argon atmosphere, reducing the exposure time to ambient conditions during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
168
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(175 citation statements)
references
References 33 publications
3
168
2
Order By: Relevance
“…9 The ZnO nanowires used in this study were grown by vaporizing and condensing a mixture of ZnO and graphite powder on carbon cloth. 11,19,20 The resulting nanowires are n-type, similar to ZnO in bulk or thin films. [15][16][17] Our technique (Figure 1) relies on the use of poly(methyl methacrylate) (PMMA) 22 as a negative resist 12,13 and electrically insulating layer.…”
mentioning
confidence: 98%
“…9 The ZnO nanowires used in this study were grown by vaporizing and condensing a mixture of ZnO and graphite powder on carbon cloth. 11,19,20 The resulting nanowires are n-type, similar to ZnO in bulk or thin films. [15][16][17] Our technique (Figure 1) relies on the use of poly(methyl methacrylate) (PMMA) 22 as a negative resist 12,13 and electrically insulating layer.…”
mentioning
confidence: 98%
“…Figure 3(d) and 3(e) reveal that ZnO crystals directly nucleate on the flat a-C film with their c-axis perpendicular to the surface of the a-C film. It is known that carbon materials such as amorphous carbon, 17 diamond, 18 graphite flakes, 19 carbon cloths, 20 and photoresists 21 can be used as preferential nucleation and growth sites for ZnO NWs. It has been suggested that the extracted Zn droplets from the reaction of ZnO/ZnO x gas with carbon materials can act as the catalysts for ZnO NW nucleation and growth on the surfaces of carbon materials.…”
mentioning
confidence: 99%
“…We have not observed any catalysts at the tips of the ZnO NWs, suggesting a self-catalytic growth. The HRTEM image recorded along the zone axis [11][12][13][14][15][16][17][18][19][20] of a NW is shown in Figure 1(d). Obviously, these ZnO NWs were structurally uniform and no crystalline defects, such as dislocations and stacking faults were observed.…”
mentioning
confidence: 99%
“…Finally for the electrical field with the assumption (P − Q)/C * ≈ 0 formulas (33) and (34) are completely analogous to (9) and (10). Therefore for the force and emission current we may use the above derived formulas.…”
Section: Simulation Of Planar Anode By "Image" Chargesmentioning
confidence: 99%
“…Recently, field emission from metals [7], metal oxides [8][9][10][11], metal carbides [12], and other elongated nanostructures have also been explored. It is now possible to control the diameter, height, radius of curvature of the tip, and basic form of emitters during growth.…”
Section: Introductionmentioning
confidence: 99%